Ultra-High-Frequency Love Surface Acoustic Wave Device for Real-Time Sensing Applications - Gina Greco; Matteo Agostini; Marco Cecchini (IEEE Access, 2020)
Love surface acoustic wave (L-SAW) devices are ideal for real-time sensing applications. High miniaturization and sensitivity are desirable in particular for point of care diagnostics or on-site measurements. It is possible to enhance both these parameters by increasing the working frequency of these devices, but this is still a challenge. Indeed, the ultra-high frequency (UHF) range has not been explored yet for L-SAW sensing devices because it requires non-trivial fabrication and measurement setup. Here, we present a multiplexable, highly miniaturized UHF L-SAW device for real-time sensing applications. The sensor performance was first tested with mixtures of different volume percentages of isopropyl alcohol (IPA) in water. Measurements of phase and amplitude (related to change of density and viscosity, respectively) show higher sensitivity and dynamic range than a representative 100 MHz L-SAW sensor. Then, we measured the adsorption kinetics of three different concentrations of bovine serum albumin (BSA) in water on the sensor surface, demonstrating biomolecule detection. The all-electrical readout system as long as the small dimensions make the presented device particularly promising for portable UHF sensing platforms. Nonetheless, the higher sensitivity and dynamic range obtained with respect to a representative 100 MHz L-SAW sensor as long as the real-time measurements of the BSA adsorption (with an estimated limit of detection of 90 ng/mm2) show that UHF Love SAW sensors have the potential to be used for bio-sensing applications, such as point of care diagnostics.